Legal Protection for Pencak Silat Athletes in the Perspective of Sports Law and Human Rights - Agustin, Noer Musdalifah; Alfath, Tahegga Primananda (Bacarita Law Journal, 2025)
Pencak Silat, Indonesia’s cultural heritage and global sport, entails intense physical contact with high injury risks. Thus, legal protection is vital to safeguard athletes’ rights and ensure fair, safe, and dignified competition. Although Indonesia has legal frameworks on sports and human rights, their implementation in protecting Pencak Silat athletes remains weak and requires urgent improvement. Purposes of the Research: Analyze the forms and mechanisms of legal protection for Pencak Silat athletes in Indonesia from the perspective of sports law. Examine the integration of legal protection with human rights principles, particularly in relation to athletes’ safety and welfare. Provide recommendations to strengthen the existing regulatory framework and improve its implementation in the field. Methods of the Research: The research employs a normative juridical approach by analyzing laws and regulations, including Law Number 11 of 2022 on Sports and Law Number 39 of 1999 on Human Rights. The study also utilizes secondary data obtained from scholarly literature, government documents, and relevant case studies. A comparative analysis is conducted to evaluate the alignment between sports law provisions and human rights protection, supported by qualitative assessment of legal practices in Indonesia. Results of the Research: Findings show Indonesia has strong legal frameworks for sports and human rights, yet protection of Pencak Silat athletes remains weak. Issues include poor supervision, limited facilities, and low legal literacy. This study’s novelty is linking sports law and human rights, recommending stronger regulations, better institutional capacity, and synchronized policies to safeguard athletes’ rights, safety, and welfare.